Chapter 5.31 The Profession of Research Management and Administration in Germany - Paul Winkler; Jens-Peter Krüger; Katrin Steinack (Emerald Publishing Limited, 2023)
This chapter provides an overview of the research management and administration (RMA) sector in Germany. It describes the German research ecosystem, looks at the – in Germany – still young profession of RMA and the professional network FORTRAMA, and provides a brief insight into the work and employment situation of people working in this field. This chapter concludes with a prognosis for the field in the upcoming years.
10.1108/978-1-80382-701-820231065; 10.1108/978-1-80382-701-820231065; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262